Glutamatergic Neurons of the Paraventricular Nucleus are Critical for the Control of Wakefulness. (15th October 2020) - Liu, Ying; Li, Ying; Yang, Bo; Yu, Minhua; Zhang, Xuefen; Bi, Linlin; Xu, Haibo
Highlights: Glutamatergic neurons of the paraventricular nucleus could regulate wakefulness. The calcium activities of PVN glutamatergic neurons increased before NREM to wake. The calcium activities of PVN glutamatergic neurons decreased before wake to NREM. Chemogenetic activation of the PVN glutamatergic neurons increased wakefulness. Chemogenetic inhibition of the PVN glutamatergic neurons decreased wakefulness. Abstract: Normal sleep–wake behavior is extremely important for humans to maintain basic physiological and cognitive activities. However, the neural mechanisms underlying sleep–wake regulation are not fully understood. The paraventricular nucleus (PVN) of the hypothalamus has been classically defined as a region for the regulation of the hypothalamoneurohypophysial system and autonomic nervous system. Here, we identify the glutamatergic neurons in the PVN that play a unique role in sleep–wake regulation. Firstly using in vivo fiber photometry, we found altered calcium activities of PVN glutamatergic neurons during three sleep state transitions in freely behaving mice. The calcium activities of PVN glutamatergic neurons began to increase before non-rapid-eye movement (NREM) sleep to wake transitions and NREM sleep to rapid-eye-movement (REM) sleep transitions and began to decrease before wake to NREM sleep transitions. Then we used chemogenetic manipulations together with polysomnographic recordings, activation of PVN neurons increased wakefulness and decreased NREM sleep, while inhibition of PVN neurons caused a reduction in wakefulness and an increase in NREM sleep. Altogether, our findings revealed an important role for PVN glutamatergic neurons in the regulation of wake state.